Less-invasive fascia-preserving surgery for abdominal wall desmoid - Yoshihiro Nishida (Nature Portfolio, 2021)
Abstract The mainstay of treatment for desmoid has been shifted to active surveillance (AS). However, surgery is still being performed on abdominal wall desmoid with a wide surgical margin. The purposes of this study are to clarify the treatment results of less-invasive, fascia preserving surgery for patients with abdominal wall desmoid, and to propose a new treatment modality. Since 2009, 34 patients with abdominal desmoid have been treated in our institution. Among them, as a final treatment modality, 15 (44%) were successful with AS, 15 were subjected to less-invasive surgery, and 4 methotrexate and vinblastine treatment. The clinical results of less-invasive surgery were clarified. In the surgical group, although the surgical margin was all microscopic positive (R1), only one patient (6.7%), who has the S45F mutation type of CTNNB1, showed recurrence, at a mean follow-up of 45 months. There were no patients with familial adenomatous polyposis (FAP)-related desmoid in this cohort. Only two patients (13%) required fascia lata patch reconstruction after removal of the tumor. In patients with non FAP-related abdominal wall desmoid, less-invasive, fascia preserving surgery is recommended as a favorable option as active treatment. Based on the results of this study, multi-institutional further research is warranted with an increased number of patients.